2011
DOI: 10.1590/s0102-695x2011005000136
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and immunomodulatory effects of the naphthoquinone 5-methoxy-3,4-dehydroxanthomegnin

Abstract: Large number of quinones has been associated with antitumor, antibacterial, antimalarial and antifungal activities. In this work we describe the effect of the naphthoquinone, 5-methoxy-3,4-dehydroxanthomegnin, on murine tumor cells (LP07 and LM2) and its immunomodulatory effect on nitric oxide (NO) production on LPS-stimulated macrophages. The results have shown that 5-methoxy-3,4-dehydroxanthomegnin was a significant inhibitor of LPS-stimulated NO generation from macrophage (inhibition percentage ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have shown that this compound has antitumor and immunomodulatory effects (Kitagawa et al, 2011), as well as anti-Helicobacter pylori and antioxidant properties http (Kitagawa et al, 2012). The antitumor effect of 5-methoxy-3,4-dehydroxanthomegnin may be enhanced by association with ascorbic acid as demonstrated by a significant cytotoxic index (CI) for McCoy cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that this compound has antitumor and immunomodulatory effects (Kitagawa et al, 2011), as well as anti-Helicobacter pylori and antioxidant properties http (Kitagawa et al, 2012). The antitumor effect of 5-methoxy-3,4-dehydroxanthomegnin may be enhanced by association with ascorbic acid as demonstrated by a significant cytotoxic index (CI) for McCoy cells.…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor activity of naturally occurring quinones is exhibited predominantly by three main groups, namely, benzoquinone, naphthoquinone, and anthraquinone [43]. Cancer cells are particularly vulnerable to treatments impairing redox homeostasis [44].…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, significant progress has been made in the screening of the quinone moiety for antitumor activity [ 24 ]. The redox cycling of the quinone moiety is implicated in the antitumor activity of anticancer compounds containing a quinone moiety [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This class of isocoumarin‐containing compounds shows a wide range of biological activities. For example, 5‐methoxy‐3,4‐dehydrosemixanthomegnin 2 shows cytotoxicity against murine mammary tumor cells (LM2, CI 50 74.6 µ m ) and lung adenocarcinoma cells (LPO7, CI 50 6.2 µ m ) while paepalantine 3 shows antimicrobial activity against bacteria including Bacillus cereus (MIC 7.5 µg mL –1 ), Staphylococcus aureus (MIC 7.5 µg mL –1 ) and Staphylococcus epidermidis (MIC 15 mg mL –1 ) . In addition, both of these isocoumarins show promising activity against the Helicobacter pylori bacterium, which is one of the main causes of chronic gastritis, peptic ulcers and possibly gastric cancer , .…”
Section: Introductionmentioning
confidence: 99%